Children's and young People's diabetes services: What works well and what doesn't? - N. Kime; S. Zwolinsky; A. Pringle; F. Campbell (Elsevier, 2022)
Objectives: The first year of care, post diagnosis, is pivotal for children and young people diagnosed with type 1 diabetes. This study evaluated a paediatric type 1 diabetes intervention, the 'First Year of Care', designed to maximise the care that newly diagnosed children and young people received. Study design: An observational mixed methods approach, underpinned by the Influencer Framework. Methods: A purposeful, non-probability sample of children and young people with type 1 diabetes and their families, and healthcare professionals were invited to take part. Data were collected through medical records of thirty-two newly diagnosed children and young people, plus thirty seven semi-structured interviews and exposure to six concurrent sources of influence through a questionnaire. Results: For many participants, HbA1c levels were within the optimal range by the time of their first clinic visit post-diagnosis and continued to stay within this range throughout the first year of care. Healthcare professionals prioritised the 'First Year of Care' intervention. Positive practices included: a cohesive and collaborative approach; patient-centred care; latest health technology and embedded structured education. Unusually, different multidisciplinary team members were located in one place.Data indicated statistically significant differences in total sources of influence score (t [35] = 2.331, p = 0.026); healthcare professionals' scores were higher compared to children. This suggests that children and young people have less social capital to self-manage their diabetes effectively. Greater encouragement and assistance from healthcare professionals and social networks may be needed. Conclusions: This paper identifies contemporary issues in practice and highlights the strengths and challenges for a paediatric diabetes intervention. The findings confirm the potential of layered approaches to behaviour change in managing type 1 diabetes across multiple domains of influence. Our study strongly suggests enhancing social motivation among children, young people and families to support successful long-term engagement in a paediatric diabetes intervention. Findings demonstrate healthcare professionals are key in delivering the intervention, along with opportunities to improve patient care, experience and outcomes.